2016
DOI: 10.1097/sap.0000000000000585
|View full text |Cite
|
Sign up to set email alerts
|

What Effect Does Self-Citation Have on Bibliometric Measures in Academic Plastic Surgery?

Abstract: Self-citation has a minor impact on common bibliometric measures in academic plastic surgery. The influence of self-citation is consistent across academic ranks and increasing levels of bibliometric measures, suggesting that authors are not manipulating the system with increasing experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 27 publications
0
39
1
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A key difference among studies is the variability of the h-index between specialties, in some cases reflecting underlying differences in academic promotion between departments or schools.…”
Section: Resultsmentioning
confidence: 99%
“…Among oral and maxillofacial surgeons and plastic and reconstructive surgeons, a recent study found that the h-index was strongly correlated with academic rank (r=0.62-0.64, p<0.001). 21,22 A fourth limitation is that our choice to exclude part-time faculty members limited our ability to assess the impact that research productivity has on academic rank among this subgroup. 20 Studies in the medical literature have yielded significant results, albeit with higher thresholds for promotion.…”
Section: Discussionmentioning
confidence: 99%
“…This problem has been evaluated in the plastic surgery literature but was not found to influence bibliometric measurements. Nonetheless, small fields like psoriatic arthritis are probably more prone to self‐citation biases given the fewer number of key authors …”
Section: Discussionmentioning
confidence: 99%
“…Second, TC inherently favors early articles whose ACs might be lowered because of citation fatigue, which might lead to some biases in analytic results. In addition, we did not pay extra attention to inappropriate citations including self‐citations, in‐house citations and content‐irrelevant citations, whose impact on bibliometric measures exists but was not considered significant in some studies . Third, reviews, guidelines, and meta‐analyses were excluded from our study to make our top 100 list an appropriate reflection of the trending of original investigations.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, we did not pay extra attention to inappropriate citations including self-citations, in-house citations and content-irrelevant citations, whose impact on bibliometric measures exists but was not considered significant in some studies. 26,27 Third, reviews, guidelines, and meta-analyses were excluded from our study to make our top 100 list an appropriate reflection of the trending of original investigations. From another perspective, these three types of article properly covered mainstream applications in their ages and the inclusion of them might exemplify the history of echocardiography development as a previous work did.…”
Section: Limitationsmentioning
confidence: 99%